Association between respirable dust exposure and respiratory health among cement workers - Kamaludin, Noor Haziqah; Ahmad Razlan, Nurul Shahira; Jalaludin, Juliana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Cement industry contributes to the major constituent of airborne dust in the atmosphere. This study aims to determine the level of respirable cement dust exposure associated with workers’ respiratory health. A cross-sectional study was carried out among 84 administration workers as the comparative group and 84 manufacturing workers as the exposed group. Method: A set of validated questionnaires was used to obtain some pertained background information as well as respiratory symptoms among the respondents. Personal Air Sampling Pump was used for assessing personal exposure towards cement dust in 8 hours. For lung function performance, a Spirometry test was carried out and Fractional Exhaled Nitric Oxide (FENO) test was conducted to assess airway inflammation. Results: The median for personal exposure level to respirable dust of manufacturing workers was 2.68 (5.90) mg/m3 with range 0.351 to 10.60 mg/m3. The lung function abnormality among the manufacturing workers was FVC% (PR=3.82, 95% CI=1.52-9.58) and FEV1% (PR=5.16, 95% CI=1.65-16.10). Cough was reported to occur the most likely among the manufacturing workers (PR=2.40, 95% CI=1.12-5.15). After adjusting the smoking status, the prevalence of phlegm and cough were 35.7% and 29.8% respectively. 16.7% of manufacturing workers recorded a high level of FENO. The increasing exposure to respirable dust significantly reduces the FVC% of manufacturing workers (r=-0.36, p=0.05). Conclusion: The personal exposure to respirable cement dust increases the risk of lung impairment by highly developing respiratory health symptoms, reducing lung function level and increasing the higher level of airway inflammation among highly exposed workers.